Memoirs about cardinol Vincent - Tamkevičius, Sigitas (Genocidas ir rezistencija, 2021)
In this text, the author shares his memories of Cardinal Vincentas Sladkevičius, the circumstances under which they met, the support the author received from the Cardinal after the Soviet government’s persecution, and how Cardinal Sladkevičius himself was persecuted by the Soviet government.
Keywords: Catholic Church; soviet Lithuania; soviet religion politics; repression; Vincentas Sladkevičius